2010
DOI: 10.1016/j.cub.2010.02.058
|View full text |Cite
|
Sign up to set email alerts
|

Motor Coordination via a Tug-of-War Mechanism Drives Bidirectional Vesicle Transport

Abstract: Summary The microtubule motors kinesin and dynein function collectively to drive vesicular transport. High resolution tracking of vesicle motility in the cell indicates that transport is often bidirectional, characterized by frequent directional changes. However, the mechanisms coordinating the collective activities of oppositely-oriented motors bound to the same cargo are not well understood. To examine motor coordination, we purified neuronal transport vesicles and analyzed their motility using automated par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
462
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(527 citation statements)
references
References 29 publications
(42 reference statements)
38
462
7
Order By: Relevance
“…It has been shown that in general, the two types of opposite motors are attached at the same time on the cargo [388,156]. Then two scenarios can be considered [151,327,40] (Fig.…”
Section: Tug-of-warmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that in general, the two types of opposite motors are attached at the same time on the cargo [388,156]. Then two scenarios can be considered [151,327,40] (Fig.…”
Section: Tug-of-warmentioning
confidence: 99%
“…As a result, the cargo will go back and forth, possibly performing large (compared to the typical motor step size) excursions in each direction [156]. An experimental observation in favour of this scenario was made on endosomes which were found to be elongated when pausing [351].…”
Section: Tug-of-warmentioning
confidence: 99%
See 1 more Smart Citation
“…4 F). The short-slow run represents motors engaged in a tug-of-war between oppositely directed molecular motors attached to the same cargo (87,88). The long-fast run (~4 mm displacement and 3 s duration, such as the movement within 305 to 308 s in phase III, Fig.…”
Section: Monitoring Egfr Trafficking From Membrane To Cytoplasm In LImentioning
confidence: 99%
“…A model of a stochastic “tug‐of‐war” that describes the mechanical competition between antagonistic motors bound to the same cargo has been proposed 15. Small changes in the number of active motors lead to significant changes in the net direction of cargo motility 16. In our study, the extra force generated by the recruitment of additional kinesin or dynein motors outcompetes the force generated by the endogenous motors, thereby enforcing cargo transport toward the cell periphery or toward the cell center (Supporting Information, Figure S13).…”
mentioning
confidence: 99%